Contemporary approaches to the search for active drugs and chemotherapy regimens for tuberculosis treatment - T. K. Lugovkinа; S. N. Skornyakov; E. I. Kildyushevа; E. A. Egorov (Туберкулез и болезни лёгких, 2020)
The article analyzes scientific publications (37 articles) devoted to phthisiology, clinical pharmacology of antimicrobial agents, laboratory methods for evaluating the effectiveness and safety of various regimens of tuberculosis chemotherapy caused by resistant strains of M. tuberculosis.It tells about prospects for expanding the line of antimicrobial agents for treatment of tuberculosis caused by resistant strains of M. tuberculosis, new approaches to the study and evaluation of the effectiveness of the drug at the stage of preclinical trials using the in vitro HFS-TV model.